2016
DOI: 10.1088/0964-1726/25/10/107002
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and investigation on field-dependent properties of natural rubber based magneto-rheological elastomer isolator

Abstract: This study presents a laminatedmagnetorheological elastomer (MRE) isolator which applies to vibration control in practice. The proposed isolator is fabricated with multilayer MRE sheets associated with the natural rubber (NR) as a matrix, and steel plates. The fabricated MRE isolator is then magnetically analysed to achieve high magnetic field intensity which can produce high damping force required for effective vibration control. Subsequently, the NR-based MRE specimen is tested to identify the field-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…On the other hand, active vibration isolation involves the application of complex structures that utilize sensors and actuators to damp out the unwanted vibrations. Notably, a new class of semi‐active vibration absorbers consisting of magnetorheological (MR) materials can offer several unique advantages such as the real‐time control of stiffness and damping, as opposed to conventional rubber, which has fixed stiffness and damping . A comparison of various properties between conventional rubber and MR elastomers is presented in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, active vibration isolation involves the application of complex structures that utilize sensors and actuators to damp out the unwanted vibrations. Notably, a new class of semi‐active vibration absorbers consisting of magnetorheological (MR) materials can offer several unique advantages such as the real‐time control of stiffness and damping, as opposed to conventional rubber, which has fixed stiffness and damping . A comparison of various properties between conventional rubber and MR elastomers is presented in Table .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a strong particle interaction, resulting from an increase in the magnetic field, can lead to the formation of large particle aggregates. The common matrix materials for MR elastomers include natural rubber, silicone rubber, polybutadiene, polyurethane (PU), and polyisobutylene rubber . On the basis of curing conditions, MR elastomers can be classified into isotropic and anisotropic .…”
Section: Introductionmentioning
confidence: 99%
“…So far, several MRE-based isolation devices have been proposed [18][19][20][21][22][23][24][25][26][27][28]. Most of the proposed MRE-based base isolators utilized silicone rubber that cures at room temperature conditions without any special equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the proposed MRE-based base isolators utilized silicone rubber that cures at room temperature conditions without any special equipment. However, silicone rubber generates air bubbles on the contact surface, resulting in poor adhesion, which reduces the concentration of the magnetic field [28]. Chen et al [29] observed that the MRE using natural rubber is superior in mechanical properties to the MRE using silicone rubber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation